Utilization of crumb rubber as a partial replacement of bitumen in flexible pavement - Kerni Chahal; Tangri Amanpreet (E3S Web of Conferences)
Crumb rubber's ability to improve asphalt surface performance, longevity, and sustainability has garnered attention in recent years. Crumb rubber is made from used tyres and can be put to asphalt mixtures to provide pavement that is more durable and resilient. The increasing rate at which tyres are being discarded is a major contributor to pollution. It can be utilized as a low-cost and environmentally friendly modification procedure to reduce pavement construction pollution. In this study, Bitumen VG 30 has been mixed with Crumb Rubber at percentages of 5%, 10%, and 15%. The Wet mix procedure was used to make the modified bitumen. The mix was designed using the Marshall Stability approach. Modified bitumen containing Crumb rubber and binder aggregate was tested for its physical characteristics. The modified mixtures made using Crumb rubber showed an increase in strength. The most successful ratios were then combined to make bituminous mix. Wheel rut test and the skid resistance were used to analyse how well the bituminous mixtures performed. Crumb rubber improved the rutting resistance of wheel rutting test samples over unmodified mix. Crumb rubber modified bituminous mix has a higher skid resistance value than unmodified.